A Scoping Review of the Oral Health Status, Oral Health Behaviours and Interventions to Improve the Oral Health of Children and Young People in Care and Care Leavers - Joelle Booth; Jo Erwin; Lorna Burns; Nick Axford; Jane Horrell; Hannah Wheat; Robert Witton; Jill Shawe; Janine Doughty; Sarah Kaddour; Skye Boswell; Urshla Devalia; et al. (MDPI AG, 2024)
Background: Children and young people (CYP) in care experience poorer physical health and overall wellbeing in comparison to their peers. Despite this, relatively little is known about what their oral health needs and behaviours are. The aim of this scoping review was to provide a global perspective on the oral health status and behaviours of CYP in care and care leavers. It also aimed to synthesise interventions that have been trialled in this population to improve oral health. Methods: Five databases were searched, Ovid Embase, Ovid MEDLINE, CINAHL (EBSCOhost), SocINDEX (EBSCOhost) and Dentistry and Oral Sciences Source (EBSCOhost), alongside grey literature sources up to January 2023. Eligibility criteria were studies that (i) reported on children and adolescents aged 25 years or younger who are currently in formal/informal foster or residential care and care leavers, (ii) pertained to oral health profile, behaviours or oral health promotion interventions (iii) and were published in the English language. Thematic analysis was used to develop the domains for oral health behaviours and interventions. Results: Seventy-one papers were included. Most papers were published from very high or medium Human Development Index countries. CYP in care were found to experience high levels of decay, dental trauma, periodontal disease and poorer oral health-related quality of life. Oral health behaviours included limited oral health self-care behaviours and a lack of oral health-based knowledge. The trialled interventions involved oral health education, supervised brushing and treatment or preventative dental care. Conclusions: This scoping review reveals that CYP in care experience poorer oral health in comparison to their peers. They are also less likely to carry out oral health self-care behaviours. This review highlights a scarcity of interventions to improve the oral health of this population and a paucity of evidence surrounding the oral health needs of care leavers.